Analisis Penagihan Tunggakan Pajak dengan Surat Teguran dan Surat Paksa untuk Meningkatkan Penerimaan Pajak pada KPP Pratama Rantau Prapat - Indri Apriani; Arnida Wahyuni Lubis; Yenni Samri Juliati Nasution (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Taxes are the largest source of revenue for the State.taxes are obligations that must be paid by the people to the state. Indonesia establishes a tax system, namely a self-assessment system where taxpayers are given the trust to calculate, pay, and report the amount of tax owed by themselves. However, there are obstacles in collecting taxes, namely the existence of tax arrears, this is due to the lack of knowledge of taxpayers regarding taxation. To overcome tax arrears the fiscus performs what is called collection to collect the amount of tax debt owed to the state by issuing letters of reprimand and forced letters.This study aims to determine the level of effectiveness of tax collection and how much tax revenue contributes from the disbursement of reprimand letters and forced letters to increase tax revenue at KPP Pratama Rantau Prapat.The method used in this study is a quantitative descriptive method and the type of data used is secondary data and primary data. Based on the results of data analysis, it can be concluded that the collection of tax arrears with letters of reprimand and forced letters is included in the category of ineffective. Keywords: collection of tax arrears,reprimand letter,forced letter,tax revenue